White Separatists and Black Separatists: A Comparative Analysis. (7th August 2014) - Feagin, Joe R.
Abstract : A major weakness in many treatments of the models, historical or contemporary, which delineate the preferred goals of interethnic and interracial adjustment in America has been the omission of separatist models. This paper focuses on certain extreme separatist models proposed in regard to black-white adjustment, first by examining the historical background, then by re-analyzing recent survey data to assess the extent to which rank-and-file white and black Americans support separatist solutions. Demographic and attitudinal correlates of separatism are also systematically examined. In the light of the surprisingly strong white support for separatism found in the survey data, the conclusion raises some questions about Parsons' view of the ongoing inclusion process.